What Explains the Rise in CEO Pay in Germany? A Panel Data Analysis for 1977-2009 - Francesca Fabbri; Dalia Marin (Ludwig-Maximilians-Universität München, Volkswirtschaftliche Fakultät, 2012)
The compensation of executive board members in Germany has become a highly controversial topic since Vodafone's hostile takeover of Mannesmann in 2000 and it is again in the spotlight since the outbreak of the financial crisis of 2009. Based on unique panel data evidence of the 500 largest firms in Germany in the period 1977-2009 we test two prominent hypotheses in the literature on executive pay: the manager power hypothesis and the efficient pay hypothesis. We find support for the manager power hypothesis for Germany as executives tend to be rewarded when the sector is doing well rather than the firm they work for. We reject, however, the efficient pay hypothesis as CEO pay and the demand for managers increases in Germany in difficult times when the typical firm size shrinks. We find further that domestic and global competition for managers has contributed to the rise in executive pay in Germany. Lastly, we show that CEOs in the banking sector are provided with incentives for performance and that the great recession of 2009 acted as a disciplining devise on CEO pay in Germany.
urn:nbn:de:bvb:19-epub-12817-2
Keywords: F23; J3; M12; M52; 330; manager power hypothesis; efficient pay hypothesis; domestic and global competition for managers; CEO pay in banks; CEO pay in the financial crisis; Managervergütung; Führungskräfte; Macht; Effizienzlohn; Corporate Governance; Schätzung; Deutschland